EFEKTIVITAS KONVENSI ILO NO. 189 TERHADAP PEKERJA RUMAH TANGGA (PRT) FILIPINA - Ningsih Silitonga; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research will analyzed the factors that influence the effectiveness implementation of ILO Convention No. 189 on decent work for domestic workers of Filipino domestic workers. This research an aim to explain role of International Labor Organisation (ILO) in programme to given of rights to Filipino domestic workersThis research is conducted by using the research methods literature where the data and information received from sources that are relevant to the research problem. This research uses neo-liberalist perspective to analyze the cooperation of the Government of the Philippines and the theory of policy implementation proposed by Merilee S. Grindle and the concept of national interest of Donald E. Nuchterlein.The results of this research describe that the effectiveness of the implementation of ILO Convention No. 189 due to the attitude of the Government Filipinna pro-active in providing relevant rules of decent work for Filipino workers. The success of the Philippine government in establishing communication with the recipients of services make the convention effective. Despite this policy excluded many people reduce labor services revenues Philippines but still Filipinna Government regulations stipulate.Keywords: Convention ILO, Domestic Worker, Effectiveness Policy